School Interventions for Bullying–Cyberbullying Prevention in Adolescents: Insights from the UPRIGHT and CREEP Projects - Silvia Gabrielli (MDPI AG, 2021)
Background: Several challenges and emotional demands characterize adolescence, affecting the mental well-being of youths. Among these, bullying and cyberbullying are recognized nowadays as a major social problem, affecting more than one-third of adolescents, with extensive negative consequences for the victims involved, such as lower self-esteem, increased loneliness, depression, and anxiety. School programs and interventions that foster resilience, coping, and well-being are particularly important during adolescence as protective and preventive factors against the consequences of (cyber)bullying. The paper presents two recent co-designed interventions for (cyber)bullying prevention deployed in Europe, targeting early adolescents and their school communities. Methods: The UPRIGHT project developed an evidence-based, whole-school intervention to train resilience as a protective factor to promote mental well-being in adolescents, in a cross-national perspective. The CREEP project designed and implemented digital interventions to support schools in (i) early detection of cyberbullying events on social media and (ii) coaching adolescents (victims, bullies, bystanders) on how to cope with (cyber)bullying behaviors. Results: The main challenges and insights collected during the design and implementation of both interventions are discussed to inform future research and practice. Conclusion: The feasibility and acceptance of prevention programs are key to the reducing risk of (cyber)bullying and improving the psychological well-being of early adolescents.